Patrick N. Lynch: third Catholic bishop of Charleston - Heisser, David C. R. (University of South Carolina Press, 2015)
Formative years -- Priest in Charleston -- Advancement in the 1850s -- Slaveholdings -- The war -- Rome mission -- Slavery treatise -- War's end and return home -- Baltimore second plenary -- Reconstruction -- 1870s to his death